Lung microbiome alterations correlate with immune imbalance in non-small cell lung cancer - Cheng, Jiuling; Wang, Huaqi (Frontiers in Immunology, 2025)
BackgroundCurrent understanding of the link between microbiota imbalance and immune function in non-small cell lung cancer (NSCLC) has not been fully elucidated. This study aims to explore the link between dysbiotic lung microbiota and immunity in NSCLC, which may provide valuable information for disease progression monitoring and prognosis prediction.MethodsLung microbial communities from both the tumor-affected (n = 43) and contralateral healthy sides (n = 38) of lung cancer patients were analyzed by 16S rRNA sequencing. The association between microbial abundance and tumor stages, metastasis or not, nodule size, PD-L1 expression, as well as Ki-67 levels was conducted. Mann-Whitney tests were used to evaluate differences in the systemic immune-inflammation index (SII), T cell subsets (CD3+, CD4+, CD8+), as well as the CD4+/CD8+ ratio between different microbial expression patterns of Prevotella and Veillonella.ResultsSignificant β-diversity differences were observed between the tumor-bearing and contralateral normal lungs in individuals diagnosed with lung carcinoma. A notable increase in Prevotella (P = 0.044) and Veillonella (P = 0.02) was detected within NSCLC-affected lungs, whereas Pseudomonas (P = 0.008) as well as Staphylococcus (P = 0.033) were significantly reduced. Increased levels of Veillonella were detected in NSCLC patients at stage IIIB-IV and were positively correlated with Ki-67 expression. Furthermore, patients with higher abundance of Prevotella and Veillonella exhibited a significantly elevated systemic immune-inflammation index (SII) compared to the lower-abundance group (P = 0.0329), while their CD8+ T cell levels were significantly decreased in the higher abundance group (P = 0.0027).ConclusionMicrobial composition differed significantly between the tumor-affected and healthy sides in lung cancer patients. Veillonella was more abundant NSCLC patients at stage IIIB-IV, while increased Prevotella and Veillonella abundance correlated positively with SII but negatively with CD8+ T cell levels. These findings provide valuable insights into tumor-associated microbiota for monitoring disease advancement, treatment stratification and prognostic assessment.